Assessing the tourism potentials of Kota Marudu and its surrounding villages, Sabah, Malaysia - Rosmalina Abdul Rashid; Hamimah Talib; Jennifer Chan Kim Lian (Journal of Sustainability Science and Management, 2024)
Assessment of the potential of tourism is a crucial element that must be considered for tourism development. This paper examines and identifies the natural resources in and around Kota Marudu, focusing on potential rural tourism destinations. Conceptually, the assessment framework is developed from the perspective of tourist demands. This study classifies tourism potential based on two indicators, namely natural resources (14 items) and historical values (10 items). Cumulative scores are ascertained by applying the weighted sum model (WSM). Consequently, eight potential tourism sites are recognised based on their natural attractions and historical values. The results also show that Kota Marudu has the highest potential score for natural attraction diversity. Based on valuable information about Kota Marudu’s potential tourism development, this study proposes specific planning strategies to tap its diverse range of natural resources and the rich cultural traits of its village communities.